The origin of negative stacking fault energies and nano-twin formation in face-centered cubic high entropy alloys. (15th March 2017) - Zhang, Y.H.; Zhuang, Y.; Hu, A.; Kai, J.J.; Liu, C.T.
Abstract: The secrets behind the exceptional mechanical properties of high entropy alloys (HEAs) at cryogenic temperatures have drawn much attention in recent years. In this work, the negative stacking fault energy of FCC CrNiCo and FeCrNiCo alloys are disclosed by first-principles calculations. We found that the negative SFEs originate from the thermodynamic metastability of FCC stacking sequence and heavily influenced by the local atomic environment, which in turn affects the formation of stacking faults and nano-twins. Graphical abstract: